Angioimmunoblastic T Cell Lymphoma Mimicking Chronic Urticaria - Mohleen Kang; Nitasha Bhatia; Adrienne Sauder; Mirela Feurdean (Case Reports in Medicine)
Angioimmunoblastic T cell lymphoma (AITL) is a rare but distinct type of T cell lymphoma with an aggressive course and high mortality. Most patients are diagnosed late in the disease and usually present with generalized lymphadenopathy. A minority have skin lesions at the time of diagnosis, more commonly in the form of nonspecific maculopapular rash with or without pruritus. We report a rare case of AITL presenting with chronic, recurrent angioedema and urticaria-like lesions and no palpable peripheral adenopathy. Primary Care physicians, dermatologists, and allergists must maintain a high index of suspicion for cutaneous manifestations of lymphoma, especially if the skin lesions are refractory to standard treatment. Timely diagnosis is essential to improve survival.